Eco-Innovation and its Determinants: A Review of the Emerging Literature - Mihaela Păcesilă; Carmen Nadia Ciocoiu (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Dubrovnik, Croatia, 7-9 September 2017, 2017)
The aim of this paper is to enrich the existing research on eco-innovation and to provide an insight into the existing body of literature on eco-innovation determinants by analyzing the most significant publications in the area and the subjects of interest. The research adopts the document analysis method summarising definitions, classifications and recent developments in the area in order to develop insights into the evolution of eco-innovation and its main determinants. The findings are general and should be used by taking into account the specificity and local conditions within each country as well as the distinct environmental areas.
Keywords: O30; O31; 330; eco-innovation; determinants; review of literature